Small and medium-sized enterprises policy in Korea from the 1960s to the 2000s and beyond. Issue 3 (1st September 2016) - Sung, Chang-Yong; Kim, Ki-Chan; In, Sungyong
ABSTRACT: Korea's economic growth is a truly remarkable one from its very humble beginning. The development and growth of small and medium-sized enterprises (SMEs) and their government policy are briefly examined herein. In short, in the 1960s and 1970s, the government policy was to help the development of SMEs, but focused on the heavy and chemical industries. In the 1980s and 1990s, many SMEs became key suppliers of various parts in the growing automobile and electronics industries. In the 2000s, various policies and initiatives for SMEs led to an explosive increase and growth of venture businesses. In the 2010s, a 'win–win' growth philosophy between large companies and SMEs was actively sought through promotions of various policies. Also, numerous efforts were made to strengthen the innovative competency of SMEs, establish fair-trading order, protect SME business area, actively promote win–win growth strategy and support for strengthening SMEs' autonomy.